The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.21037/cdt.2016.04.02
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular failure predicted from right bundle branch block: cardiac magnetic resonance imaging validation

Abstract: Background: Right ventricular (RV) failure has proven to be independently associated with adverse outcomes. Electrocardiographic parameters assessing RV function are largely unknown, making echocardiography the first line for RV function assessment. It is however, limited by geometrical assumptions and is inferior to cardiac magnetic resonance imaging (CMRI) which is widely regarded as the most accurate tool for assessing RV function. Methods:We seek to determine the correlation of ECG parameters of right bund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…However, some authors argue for the existence of significant impact of RBBB on both right and left ventricular systolic function. [68][69][70] Besides, there is a growing interest in cardiac resynchronization therapy in patients with failing systemic RV, signifying the possibility to restore the mechanical synchronization of contractility in both ventricles of the heart. 71 While the duration and fragmentation of QRS complex is an established risk factor for sudden cardiac death in patients with tetralogy of Fallot, in the study by Shen et al…”
Section: Conductive System Disorders and Ventricular Ectopic Activity...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, some authors argue for the existence of significant impact of RBBB on both right and left ventricular systolic function. [68][69][70] Besides, there is a growing interest in cardiac resynchronization therapy in patients with failing systemic RV, signifying the possibility to restore the mechanical synchronization of contractility in both ventricles of the heart. 71 While the duration and fragmentation of QRS complex is an established risk factor for sudden cardiac death in patients with tetralogy of Fallot, in the study by Shen et al…”
Section: Conductive System Disorders and Ventricular Ectopic Activity...mentioning
confidence: 99%
“…The clinical significance of the RBBB remains controversial, and in clinical practice it is mostly treated as benign in terms of prognosis. However, some authors argue for the existence of significant impact of RBBB on both right and left ventricular systolic function 68–70 . Besides, there is a growing interest in cardiac resynchronization therapy in patients with failing systemic RV, signifying the possibility to restore the mechanical synchronization of contractility in both ventricles of the heart 71 .…”
Section: Introductionmentioning
confidence: 99%
“…8 In patient with RBBB, QRS width was inversely related with RV function appreciated on cardiac magnetic resonance imaging (CMR). 9 Furthermore, several studies have shown that RBBB has independent association with decreased RV function and which in itself is a predictor of adverse outcomes in patients with acquired heart disease. 10,11 However, very few numbers of study were available regarding Isolated RBBB and their impact on right ventricle morphology and function.…”
Section: Introductionmentioning
confidence: 99%